What is the answer for question 10) ?

http://postimg.org/image/yap8msn29/

### 1 Answer | Add Yours

Ans. Given `f(x)=(.8)^x`

1. `g(x)=-(.8)^x-2`

substitute `(.8)^x =f(x) ` in g(x) ,we get required transformation.

`g(x)=-f(x)-2`

2. Substitute `` in h(x) , we get required

transformation.

h(x)=(1/2) (1/.8)^2 f(x)

=(1/1.28) f(x)

3. Substitute `` in k(x) ,we get required transformation.

k(x)=(.8)^(.3x+9)

=((.8)^(x))^(.3).(.8)^9

=( f(x))^(.3). (.8)^9

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes